UJI AKTIVITAS SCALP SCRUB EKSTRAK ETANOL DAUN JAMBU METE (Anacardium occidentale L.) TERHADAP JAMUR PENYEBAB KETOMBE (Pityrosporum ovale) - Teofilia Alvanes Kronikel Gea; Novena Adi Yuhara; Ellsya Angeline Rawar (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
A scalp that is indicated to be unhealthy will damage the aesthetics of the hair. One indication of an unhealthy scalp is dandruff. Dandruff is flaking of the scalp accompanied by itching. Dandruff is caused by the abnormal development of the fungus P.ovale. Cashew leaves have bioactive compounds that have the potential to act as antifungals including flavonoids, tannins, phenolics, saponins. The aim of this research was to determine the characteristics of the scalp scrub cream preparation of cashew leaf ethanol extract and to test the potential activity of cashew leaf ethanol extract scalp scrub against the P. ovale fungus. This research uses the agar diffusion method with the well technique used in this research. Testing began by testing the potential activity of cashew leaf ethanol extract against the P. ovale fungus with concentrations of 25, 50, and 75%, then the best concentration was selected, formulated and tested for antifungal activity. The results obtained in this study were that cashew leaf extract had an inhibitory power in the strong category, namely 25% (14.57 mm ), 50% (14.9 mm ), 75% (16.63 mm ) against P. ovale. Apart from that, the results of the analysis using the Kruskal Wallis test of the scalp scrub cream preparation of cashew leaf extract at concentrations of 25%, 50%, 75% can inhibit P. each concentration variation in inhibiting P. ovale. . The conclusion of this research is that variations in the concentration of cashew leaf extract cream have antifungal activity against P.ovale